The W-Si High Precision Preshower Detector of the FASER Experiment at the LHC - Hayakawa Daiki (EPJ Web of Conferences)
FASER is searching for light, weakly-interacting particles at the Large Hadron Collider. The first search for Axion-like particles (ALPs) decaying to a photon pair using data collected in 2022 and 2023 was performed and successfully excluded regions not previously ruled out. To further reduce neutrino background, a new preshower detector will be installed by the end of 2024. The detector is based on a monolithic active pixel sensor in 130 nm SiGe BiCMOS, which will allow resolving the photon pairs interacting in the preshower detector. The final ASICs have been produced in May 2024 and are currently being validated.